2012
DOI: 10.4025/actascianimsci.v34i4.13775
|View full text |Cite
|
Sign up to set email alerts
|

Bromatological characteristics and in vitro digestibility of four sugarcane varieties subjected or not to the application of quicklime

Abstract: The experiment was conducted to evaluate the bromatological characteristics and the in vitro digestibility of four sugarcane varieties, subjected or not to hydrolysis, with quicklime. A completely randomized design was employed with three replications arranged in a 4 × 2 factorial scheme, with four sugarcane varieties (SP 52454, RB 867515, RB 855536 and IAC 862480), hydrolyzed or not. There was significant effect on brix (p < 0.05) and industrial fiber (p < 0.05), and IAC 862480 variety had the lowest levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
2
4
1
1
Order By: Relevance
“…Lignin content remained the same among varieties (Table 3). Similar results were described by Oliveira et al (2012), when analyzing NDF, ADF and lignin contents in four sugarcane varieties (RB72454, RB867515, RB855536 and IAC86-2480). The values were not statistically different and average levels were similar to this experiment.…”
Section: Neutral Detergent Fiber (Ndf) Acid Detergent Fiber (Adf) Ansupporting
confidence: 68%
“…Lignin content remained the same among varieties (Table 3). Similar results were described by Oliveira et al (2012), when analyzing NDF, ADF and lignin contents in four sugarcane varieties (RB72454, RB867515, RB855536 and IAC86-2480). The values were not statistically different and average levels were similar to this experiment.…”
Section: Neutral Detergent Fiber (Ndf) Acid Detergent Fiber (Adf) Ansupporting
confidence: 68%
“…There was not a significant difference (P>0.05) for the neutral detergent fiber and acid detergent fiber contents between the studied varieties, with values similar to those observed by Oliveira et al (2012), who obtained NDF values that varied from 35 to 63% and ADF values that varied from 21 to 36%. Averages followed by an lowercase letter in the columns do not differ by Tukey's test at a 5% significance level.…”
Section: Yield and Nutritional Value Of Plant Cane -Year Isupporting
confidence: 67%
“…Crude Protein -1 st and 2 nd Ratoon crops Oliveira et al (2012) evaluated the bromatological composition and in vitro digestibility of four sugarcane varieties, including RB 867515, and found a CP content that varied from 2.39 to 2.52%. No effect of the cutting year was observed on the CP contents for the varieties and nitrogen doses.…”
Section: Dry Matter Content In the Stems -1 St And 2 Nd Ratoon Cropsmentioning
confidence: 99%
“…This lack of difference is due to the balance of the diet, since there were different proportions of forage and concentrate to balance the energy, as can be observed with the NDFcp contents of the diets in Table 2. The values found for CNDFcp in %BW of 1.09%BW are below values found in the literature, in which, Oliveira et al (2012) reported in a literature review the overall average for the intake of 1.6% NDF in relation to the body weight.…”
Section: Resultscontrasting
confidence: 46%